Synthesis of Carboxyl (CNT-COOH) and Ammine Carbon Nanotubes (CNT-NH2) - Pardoyo, Pardoyo; Suharini, Sri Eny; Nandiyah, Siti; Subagio, Agus (JURNAL SAINS DAN MATEMATIKA, 2015)
A research synthesizing CNT-COOH to increase the compatibility character of carbon nanotubes and CNT-NH2 to increase the hydrophilic character has been done. The CNT-COOH was synthesized using ultrasonic bath method for 6 hours with the volume ratio of concentrated H2SO4 : HNO3 were 2:1, 3:1 and 4:1. Whereas CNT-NH2 was produced by refluxing CNT and ethylene diamine at temperature of 40°C, 60°C and 80°C. Both products were analyzed with Fourier Transform Infrared (FTIR), Scanning Electron Microscopy (SEM) and Energy Dispersive X-Ray Spectroscopy (EDS). The C=O bond on CNT-COOH was showed by wavenumber of 1635.64 cm-1 and the OH bond at 3448.72 cm-1 whilst the N-H bond emerged at 152762 cm-1. SEM and EDS indicated both products had surface morphology of tubes and reducing of Fe content which was the one of impurities of CNT.